Practical generation of common random strings for secure multiparty computations over the Internet - Vajda, István (Discoveries in Agriculture and Food Sciences, 2020)
It is known that most of the interesting multiparty cryptographic tasks cannot be implemented securely without trusted setup in a general concurrent network environment like the Internet. We need an appropriate trusted third party to solve this problem. An important trusted setup is a public random string shared by the parties. We present a practical n-bit coin toss protocol for provably secure implementation of such setup. Our idea is inviting external peers into the execution of the protocol to establish an honest majority among the parties. We guarantee security in the presence of an unconditional, static, malicious adversary. Additionally, we present an original practical idea of using live public radio broadcast channels for the generation of common physical random source.